Removal of servants of the Judicial Power of Paraíba located in the district of the 6th region (Research, Society and Development, 2022)
The entry of effective public servants in their positions occurs through a public contest, with appointment being one of the original forms of provision. After the effective exercise, demands may arise that cause the removal of human resources in the public service. The aim of this research is to analyze the contributory reasons for the removal of the servers of the State Judiciary of Paraíba crowded in the following counties: Água Branca, Coremas, Itaporanga, Patos, Piancó, Princesa Isabel, Santa Luzia, Taperoá and Teixeira. This is an exploratory-descriptive field research, using direct observation, bibliographic research and interviews with civil servants who occupy effective positions in the 6th region of the Court of Justice of Paraíba. In the study, we considered three dimensions to analyze agreement in relation to the contributory reasons for the removal of civil servants: organizational, environmental, and behavioral. The analysis of the results showed the need to implement the following actions: study of salaries paid by other courts of Justice of the same size/financial resources to point out any differences and correct them; insertion of bonuses for civil servants working in difficult-to-provide districts; encourage teleworking; group dynamics; quarterly analysis of computer equipment/air conditioning; performance evaluation programs and periodic meetings between judges and civil servants.